PERTUMBUHAN BAKTERI Bacillus cereus STRAIN IMB-10 PADA KONSENTRASI pH YANG BERBEDA DALAM MENDEGRADASI BAHAN BAKAR SOLAR SEBAGAI RANCANGAN MEDIA POSTER PELAJARAN BIOLOGI SMA - Widodo, Teguh Juliantani; Sayuti, Irda; Zulfarina, Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study tried to determine the growth of bacteria Bacillus cereus Strain IMB-10 at different pH concentrations in degrading diesel fuel as a poster’s media design for Biology subject in high school. Research was carried out in FKIP PMIPA laboratory, Riau University. As for the TPH testing, it was conducted in the solid waste laboratory and B3 Faculty of Civil and Environmental Engineering, Bandung Institute of Teknology. This research was conducted in 2 stages, namely research on the growth of the bacteria Bacillus cereus Strain IMB-10 at different pH in degrading diesel fuel and the stage of potential analysis and design of poster as a learning media from the research results. This research was conducted in November 2019 - June 2020. The study was designed with a completely randomized design with 3 treatments and 3 replication groups. The media used were SMSS media with the addition of variations in pH 6.5, pH 7.0, pH 7.5, which added 5% diesel fuel and the bacteria Bacillus cereus strain IMB-10. The test parameter was the OD growth of Bacillus cereus bacteria Strain IMB-10 which was seen using a spectrophotometer for 6 days measuring. Meanwhile in measuring the degradation rate (Total Petroleum Hydrocarbon) TPH of diesel fuel the Gravimetric method used. Based on the research, it was found that pH 7.0 was the best pH for the growth of Bacillus cereus bacteria Strain IMB-10 with a bacterial growth OD of 5.8 A on day 5 and a degradation rate of diesel fuel of 26.95%. Based on the analysis of the potential results of experimental research, it can be used as a learning media design for Biology posters on bacteria theory in class X Senior High School. KD 3.5 Identifying the structure, way of life, reproduction and the role of bacteria in life.Key Words: Bacteria Bacillus cereus IMB-10, pH concentration, degradation, diesel fuel, posters